2017
DOI: 10.7324/japs.2017.70917
|View full text |Cite
|
Sign up to set email alerts
|

Predictive mathematical modeling for EC50 calculation of antioxidant activity and antibacterial ability of Thai bee products

Abstract: Antioxidant activities of bee products from Thailand (honey, bee pollen and propolis) via the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulphonate)(ABTS) assays were determined. The prediction of the EC50 (the half maximal effective concentration) were studied using the logistic, sigmoidal, dose response, and asymmetric 5 parameters (5P) regression models. The antimicrobial ability was tested against Staphylococcus aureus (TISTR 517), Bacillus cereus (TISTR 687), and Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The EC 50 values of bee pollen was 2.62 ± 0.09 mg/mL. This value indicates a good antioxidant activity and higher that the values reported by some authors (Negri, Barreto, Sper, Carvalho, & Campos, 2018;Suriyatem R., Auras R. A., Intipunya P., 2017).…”
Section: Bee Pollen Characterizationmentioning
confidence: 49%
“…The EC 50 values of bee pollen was 2.62 ± 0.09 mg/mL. This value indicates a good antioxidant activity and higher that the values reported by some authors (Negri, Barreto, Sper, Carvalho, & Campos, 2018;Suriyatem R., Auras R. A., Intipunya P., 2017).…”
Section: Bee Pollen Characterizationmentioning
confidence: 49%
“…Previous research showed that bee pollen had a high antioxidant capacity (Almedia et al, 2017;Campos et al, 2003;Suriyatem et al, 2017;Sun et al, 2017;Mărghitaş et al 2009;Carpes et al, 2007) that varies due to the ecological diversity and predominance of the plant species that it was collected from. However, there is no direct correlation available between the total phenolic content (TPC) and the antioxidant capacity (Özkök & Silici, 2017;Dorman et al, 2003;Miliauskas et al, 2004).…”
Section: Antioxidant Capacities and In Vitro Bioaccessibilities Of Thmentioning
confidence: 99%
“…Table 2 shows the half-maximal effective concentration (EC 50 ) of the extracts and fractions of C. nutans leaves. The EC 50 is the concentration of antioxidant that causes a 50% decrease in radical absorbance, which is commonly assessed by measuring antioxidant concentration readings [24]. Trolox, which is a well-known natural antioxidant, was used as the standard.…”
Section: Antioxidant Capacitiesmentioning
confidence: 99%
“…However, none of the crude and fraction extracts of C. nutans leaves followed the criteria of the National Cancer Institute, which requires a crude plant extract to have an IC 50 < 30 µg/mL for preliminary assay [44]. The cell viability assay was repeated using the CN-Dcm fraction extract for different incubation times (24,48, and 72 h). The IC 50 values for the three time points were plotted ( Figure 2c) and show that at 24 h of treatment, CN-Dcm inhibited 50% of cell proliferation at a concentration of 76.93 ± 0.21 µg/mL, while at 48 h the IC 50 of the extract was 74.38 ± 0.19 µg/mL and at 72 h it was 65.95 ± 0.14 µg/mL.…”
Section: Antiproliferative Assaymentioning
confidence: 99%
See 1 more Smart Citation